(untitled) (Architecture Image Studies, 2025)
San people are a race that has existed in harsh conditions for tens of thousands of years. Despite the atmospheric and geographical conditions, these people have survived with their knowledge, arts, designs and productions that have been passed down from generation to generation. This study is basically shaped by examining, analysing and analysing the art and design commodities of the San people in terms of function. At the point of understanding this basic situation, the contexts of each design object with culture and life have been investigated. Field research (observation), visual interpretation and analysis as well as literature review were frequently used in making sense of culture-life and commodity relations and producing information. In the study, examples of innovative design approaches to conventional problems were discussed in detail, while some designs were not included in the study. Form-design-use analyses for the related instruments were examined by comparing them with modern commodities, and discussed in terms of material and production. The initial question of the study is to explore how culture and reality combine with function and reach design with the knowledge of experience through San’lar. As a result, a design strategy is explained through conventional, traditional and innovative realities, detailed analyses of the designs of San people are made, the behavioural patterns of these analyses are revealed and a research technique is proposed to designers and design students working on innovation.